Mecanismos percepto-motores em crianças com Transtorno de Déficit de Atenção com Hiperatividade: impacto no desempenho motor e cognitivo? - Bruna Silva Avelar (2019)
The studies presented in this dissertation aimed to investigate deficits in the perceptual-motor mechanisms of children with Attention-Deficit Hyperactivity Disorder (ADHD) as well as its impact on motor and cognitive task performance. The first study investigated deficits in the perceptual ability of children with ADHD. Specifically, it was evaluated whether these children show differences in performance in perceiving the length by dynamic touch when compared to typical development (TD) children. And yet, if these differences can be explained by differences in the subtle patterns of temporal fluctuations that support the extraction of information relevant to success in the perception of object properties by dynamic touch. Forty-two children (ADHD Group: 21; TD Group: 21) were asked to erceive and inform, without assistance of vision, the length of rods that varied in relation to length and magnitude of the first main moment of inertia (I1). Three-dimensional displacements of hand and rod positions were submitted to Detrended Fluctuation Analysis to estimate trial-by-trial temporal correlations. Linear mixed-effect regression model was used to estimate the contributions of I1, wielding dynamics (fractal scaling of hand and rod), Group (ADHD, TD), and the interactions between these factors to rial-by-trial variations in length reports. Children with ADHD reported shorter length for rods with higher I1, indicative of reduced sensitivity to mechanical information supporting dynamic touch. In addition, temporal correlations in wielding dynamics moderated childrens usage of I1. The second study aimed to investigate the impact of postural flexibility on the motor and cognitive performance of children with ADHD. Specifically, it was evaluated whether children with ADHD had reduced postural flexibility uring the execution of a dual-task, and if this flexibility could explain differences in performance when compared to TD children. Thirty-four children (ADHD group: 17; TD Group: 17) were asked to perform concurrently a reciprocalaiming task with two levels of demand (lower / higher difficulty) and a -back task on a force plate. The displacement of the center of pressure was submitted to Sample Entropy analysis in each experimental condition to measure the postural flexibility. Two linear regression models tested the predictive value of postural flexibility on motor and cognitive performance separately. Finally, cluster analysis characterized the children in relation to the outcome variables of the present study. Children with ADHD had lower postural flexibility, and this lower flexibility, in turn, explained the worse motor and cognitive performance compared to TD children. In addition, different motor and cognitive behaviors were verified in children with ADHD and TD children. The results of both studies indicate that children with ADHD have deficits in the perceptual-motor mechanisms that support the organization of the action, which helps to understand the functional difficulties of these children. This knowledge contributes to broadening the evaluation procedures and adjusting intervention plans for this health condition.